Electrode and secondary battery including the same
The use of a carbon nanotube structure with hydrogenated nitrile rubber in the electrode active material layer addresses conductivity and dispersion issues, enhancing battery efficiency and lifespan by forming a network structure for improved adhesion and conductivity.
Patent Information
- Application Number
- CN202411311882.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-28
- Filing Date
- 2020-03-27
- Publication Date
- 2024-12-27
AI Technical Summary
Existing conductive agents in secondary batteries, such as carbon black, carbon nanotubes, and graphene, face limitations in conductivity, dispersion, and electrolyte mobility, leading to reduced battery efficiency and life characteristics.
An electrode active material layer comprising hydrogenated nitrile rubber and a carbon nanotube structure with 2 to 5,000 single-walled carbon nanotube units, forming a network structure to enhance conductivity and adhesion.
The electrode achieves improved conductivity, reduced resistance, and enhanced life characteristics by maintaining the integrity of the carbon nanotube structure during battery operation, ensuring a strong conductive path and stable electrode adhesion.
Smart Images

Figure CN119208510A_ABST
Abstract
Description
[0001] This application is a divisional application of a Chinese patent application filed on March 27, 2020, with application number "202080026696.9" and invention name "Electrode and secondary battery comprising the electrode".
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims the benefit of priority to Korean Patent Application No. 10-2019-0035776, filed on Mar. 28, 2019, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0004] The present invention relates to an electrode and a secondary battery including the electrode, and more specifically, to an electrode and a secondary battery including an electrode active material layer, wherein: the electrode active material layer includes an electrode active material, hydrogenated nitrile rubber and a conductive agent; the conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined; and the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %. Background Art
[0005] A typical example of an electrochemical device using electrochemical energy may be a secondary battery, and the trend is that its use range is becoming wider and wider. In recent years, with the technological development and increased demand for portable devices such as portable computers, mobile phones, and cameras, the demand for secondary batteries as energy sources has greatly increased, and among these secondary batteries, lithium secondary batteries having high energy density, i.e., high capacity, have been extensively studied and commercialized and widely used.
[0006] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte and a separator. The positive electrode and the negative electrode are generally composed of an electrode current collector and an electrode active material layer formed on the electrode current collector, and the electrode active material layer is prepared by coating an electrode slurry composition including an electrode active material, a conductive agent, a binder, etc. on the electrode current collector, drying it, and then winding it.
[0007] Meanwhile, generally, point-type conductive agents such as carbon black have been mainly used as conductive agents for secondary batteries, but there are limitations because such point-type conductive agents do not have a sufficient effect of improving conductivity. In order to overcome such limitations, research on methods of applying linear conductive agents such as carbon nanotubes (CNT) and carbon nanofibers (CNF) and planar conductive agents such as graphene has been actively conducted.
[0008] However, linear conductive agents such as carbon nanotubes or carbon nanofibers have excellent conductivity, but due to the characteristics of the material itself grown in a bundle or entangled form, the dispersion in the slurry is poor, so that the coating performance and processability are deteriorated, and the linear conductive agent cannot be uniformly distributed in the electrode active material layer, which has limitations. In order to overcome such limitations, attempts have been made to improve the dispersion by introducing functional groups into the linear conductive agent, but in this case, there is a limitation because the presence of the functional groups causes surface side reactions, thereby deteriorating the electrochemical characteristics.
[0009] Meanwhile, planar conductive agents such as graphene also have excellent conductivity, but there are limitations because it is difficult to produce a single layer of graphene with a thin thickness, and if a graphene with a thick thickness is used, the battery efficiency is reduced. In addition, in the case of a planar conductive agent, there are limitations because the mobility of the electrolyte in the battery is limited due to the wide planar contact.
[0010] Therefore, there is a need to develop an electrode coated with a conductive agent that has excellent conductivity and can be uniformly distributed in the electrode. Summary of the invention
[0011] Technical issues
[0012] One aspect of the present invention provides a novel electrode that can greatly improve conductivity in a battery and can improve life characteristics of the battery due to excellent electrode adhesion.
[0013] Another aspect of the present invention provides a secondary battery including the electrode.
[0014] Technical Solution
[0015] According to one aspect of the present invention, there is provided an electrode comprising an electrode active material layer, wherein the electrode active material layer comprises an electrode active material, hydrogenated nitrile rubber and a conductive agent, the conductive agent comprises a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined, and the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %.
[0016] According to another embodiment of the inventive concept, a secondary battery including the electrode is provided.
[0017] Beneficial Effects
[0018] Since the electrode according to the present invention is prepared by using a conductive agent dispersion in which a bundle-type single-walled carbon nanotube is appropriately dispersed using hydrogenated nitrile rubber, the carbon nanotube structure in a rope shape (long fiber shape) can be connected to each other to form a network structure in the electrode. In particular, since a network structure can be formed so that a conductive connection (relatively long distance) can be made between electrode active materials in the form of secondary particles and between primary materials in the electrode active materials, a conductive path in the electrode can be effectively formed. Therefore, even with a very small amount of conductive agent, the conductivity in the battery can be greatly improved. In addition, the electrode active material layer is firmly fixed by the carbon nanotube structure forming a network structure, thereby having the effect of improving electrode adhesion.
[0019] Furthermore, when the electrode slurry includes the carbon nanotube structure, the powder resistance of the electrode slurry is reduced compared to the prior art, thereby achieving the effect of reducing the electrode resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a TEM photograph of the electrode of Example 1.
[0021] Figure 2 is a SEM photograph taken after drying the conductive agent dispersions of Preparation Examples 1 to 5 on a silicon wafer (Preparation Examples 1 to 5 correspond to Figure 2 A to 2E).
[0022] Figure 3 Preparation Example 1 ( Figure 3 A) and Preparation Example 6 ( Figure 3 B) after drying the conductive agent dispersion (Preparation Examples 1 to 5 correspond to Figure 2 A to 2E).
[0023] Figure 4 is a photograph showing the process of leaving the conductive agent dispersions of Preparation Examples 1 to 5 for 2 weeks (Preparation Examples 1 to 5 correspond to Figure 4 A to 4E).
[0024] Figure 5 is a TEM photograph of each conductive agent dispersion used in Example 1 and Comparative Example 4, and Example 1 ( Figure 5 A) and Comparative Example 4 ( Figure 5 B) SEM images of each positive electrode. DETAILED DESCRIPTION
[0025] The terms or words used in the present specification and claims should not be construed as limited to the ordinary meaning or dictionary meaning, but should be construed as meanings and concepts consistent with the technical spirit based on the principle that the inventor can appropriately define the concepts of the terms in order to interpret the present invention in the best manner.
[0026] The terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to be limiting of the present invention. Terms in the singular may include plural forms unless the context clearly indicates otherwise.
[0027] It should be understood that when used in this specification, the terms "comprises", "comprising" or "having" specify the presence of stated features, numbers, steps, elements or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements or a combination thereof.
[0028] In the present specification, unless specifically stated otherwise, the expression "%" means wt %.
[0029] In this specification, the expression "specific surface area" is measured by the BET method, wherein, specifically, the specific surface area can be calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77K) using BELSORP-mini manufactured by Bell Japan.
[0030] Hereinafter, the present invention will be described in detail.
[0031] electrode
[0032] The electrode according to the present invention includes an electrode active material layer, wherein the electrode active material layer includes an electrode active material, hydrogenated nitrile rubber and a conductive agent, the conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined, and the carbon nanotube structure can be included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %.
[0033] The electrode may include an electrode active material layer. The electrode may further include a current collector, and in this case, the electrode active material layer may be provided on one surface or both surfaces of the current collector.
[0034] There is no particular limitation on the current collector as long as the material of the current collector has conductivity and does not cause adverse chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, alloys thereof, these materials surface-treated with carbon, nickel, titanium, silver, etc., calcined carbon, etc. can be used.
[0035] The current collector can generally have a thickness of 3 μm to 500 μm, and minute unevenness can be formed on the surface of the current collector to improve the adhesion of the electrode active material. In addition, for example, the current collector can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, non-woven fabrics, etc.
[0036] The electrode active material layer can include an electrode active material, hydrogenated nitrile rubber, and a conductive agent.
[0037] The electrode active material can be a positive electrode active material or a negative electrode active material commonly used in the art, and there is no particular limitation on its type.
[0038] For example, at least one metal such as cobalt, manganese, nickel, or aluminum and a lithium-containing lithium oxide can be used as the positive electrode active material. Specifically, the lithium oxide can include lithium manganese-based oxides (e.g., LiMnO2, LiMn2O, etc.), lithium cobalt-based oxides (e.g., LiCoO2, etc.), lithium nickel-based oxides (e.g., LiNiO2, etc.), lithium nickel manganese-based oxides (e.g., LiNi 1-Y1 Mn Y1 O2 (where 0 < Y1 < 1), LiNi Z1 Mn 2-Z1 O4 (where 0 < Z1 < 2), etc.), lithium-nickel cobalt-based oxides (e.g., LiNi 1-Y2 Co Y2 O2 (where 0 < Y2 < 1), etc.), lithium manganese cobalt-based oxides (e.g., LiCo 1-Y3 Mn Y3 O2 (where 0 < Y3 < 1), LiMn 2-Z2 Co z2 O4 (where 0 < Z2 < 2, etc.), lithium nickel cobalt manganese-based oxides (e.g., Li(Ni P1 Co Q1 Mn R1 )O2 (where 0 < P1 < 1, 0 < Q1 < 1, 0 < R1 < 1, and P1 + Q1 + R1 = 1) or Li(Ni P2 Co Q2 Mn R2 )O4 (where 0 < P2 < 2, 0 < Q2 < 2, 0 < R2 < 2, and P2 + Q2 + R2 = 2), etc.), or lithium nickel cobalt manganese other metal (M) oxides (e.g., Li(Ni P3 Co Q3 Mn R3 M 1 S)O2 (where M1 is selected from the group consisting of l, Cu, Fe, V, Cr, Ti, Zr, Zn, Ta, Nb, Mg, B, W, and Mo, and P3, Q3, R3, and S are atomic fractions of each independent element, where 0 < P3 < 1, 0 < Q3 < 1, 0 < R3 < 1, 0 < S < 1, and P3 + Q3 + R3 + S = 1), etc.), and may include any one of them or two or more of them.
[0039] Meanwhile, the negative electrode active material may include, for example: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; and metal compounds alloyable with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; metal oxides that may or may not be doped with lithium such as SiO v (0 < v < 2), SnO2, vanadium oxides, and lithium vanadium oxides; or composites including metal compounds and carbonaceous materials such as Si-C composites or Sn-C composites; any one of them or a mixture of two or more of them may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material.
[0040] The electrode active material may be included in an amount of 70% by weight to 99.5% by weight, preferably 80% by weight to 99% by weight, based on the total weight of the electrode active material layer. When the content of the electrode active material satisfies the above range, excellent energy density, electrode adhesion, and conductivity can be achieved.
[0041] The conductive agent may include a carbon nanotube structure.
[0042] The carbon nanotube structure may include a plurality of single-walled carbon nanotube units. Specifically, the carbon nanotube structure may be a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and more specifically, the carbon nanotube structure may be a carbon nanotube structure in which 2 to 4,500 single-walled carbon nanotube units are bonded to each other. More specifically, considering the dispersibility of the carbon nanotube structure and the durability of the electrode, most preferably, the carbon nanotube structure is a carbon nanotube structure in which 2 to 50 single-walled carbon nanotube units are bonded to each other.
[0043] In the carbon nanotube structure, the single-walled carbon nanotube units may be arranged side by side (where the long axes of the units are bonded to each other in parallel to have a flexible cylindrical structure) to form the carbon nanotube structure. Therefore, the carbon nanotube structure may exhibit a rope-like shape. In addition, the carbon nanotube structures may be connected to each other to form a network structure in the electrode.
[0044] Conventional electrodes including carbon nanotubes are prepared by dispersing bundle type or entangled type carbon nanotubes (in the form of single-walled carbon nanotube units or multi-walled carbon nanotube units attached or entangled to each other) in a dispersion medium to prepare a conductive agent dispersion, and then using the conductive agent dispersion. In this case, the carbon nanotubes are completely dispersed in a typical conductive agent dispersion, thereby existing as a conductive agent dispersion in which carbon nanotube units in a single chain form are dispersed. In conventional conductive agent dispersions, the carbon nanotube units are easily cut by an over-dispersion process, so that the length of the carbon nanotube units is less than the initial length. In addition, the carbon nanotube units are also easily cut in the rolling process of the electrode, and another limitation occurs, in which the carbon nanotube units are cut due to excessive volume changes of the electrode active material during battery operation. Therefore, due to the deterioration of the conductivity of the electrode, there is a limitation that the input characteristics, output characteristics and life characteristics of the battery are deteriorated. In addition, for multi-walled carbon nanotube units, due to the mechanism of node growth (not a smooth linear shape, but nodes exist due to defects generated during the growth process), the structural defects are high. Therefore, during the dispersion process, the multi-walled carbon nanotube units are more easily cut, and the cut multi-walled carbon nanotube units may agglomerate with each other via the π-e stacking of the carbon of the unit. Therefore, it is difficult to make the multi-walled carbon nanotube units more uniformly dispersed and present in the electrode slurry.
[0045] Alternatively, since the carbon nanotube structure included in the electrode of the present invention has a form in which 2 to 5,000 single-walled carbon nanotube units are combined side by side with each other and relatively maintain high crystallinity without structural defects, the length thereof can be well maintained without being cut even during battery operation, so that the conductivity of the electrode can be maintained. In addition, since the high conductivity of the single-walled carbon nanotube unit with high crystallinity leads to an increase in the conductivity of the electrode, the input characteristics, output characteristics and life characteristics of the battery can be significantly improved. In addition, since the carbon nanotube structure can be connected to each other to have a network structure in the electrode, the excessive volume change of the electrode active material can be suppressed, and at the same time a strong conductive path can be ensured, and the peeling of the electrode active material can be suppressed to significantly improve the electrode adhesion.
[0046] In the carbon nanotube structure, the average diameter of the single-walled carbon nanotube unit can be 0.5nm to 10nm, particularly 1nm to 9nm. In the case of satisfying the average diameter, even with a very small amount of conductive agent, it has the effect of maximizing the conductivity in the electrode. When the prepared electrode is observed by SEM, the average diameter corresponds to the average value of the diameters of the first 100 single-walled carbon nanotubes having a large diameter and the last 100 single-walled carbon nanotubes having a small diameter.
[0047] In the carbon nanotube structure, the average length of the single-walled carbon nanotube unit can be 1 μm to 100 μm, particularly 5 μm to 50 μm. When the average length is met, since a long conductive path for conductive connection between the electrode active material particles can be formed and a unique network structure can be formed, even with a very small amount of conductive agent, it has the effect of maximizing the conductivity in the electrode. When the prepared electrode is observed by SEM, the average length corresponds to the average value of the lengths of the first 100 single-walled carbon nanotubes with long lengths and the last 100 single-walled carbon nanotubes with short lengths.
[0048] The specific surface area of a single-walled carbon nanotube unit can be 500m 2 / g to 1,000m 2 / g, especially 600m 2 / g to 800m 2 / g. When the above range is met, the conductive path in the electrode can be smoothly ensured due to the large specific surface area, so even if a very small amount of conductive agent is used, it has the effect of maximizing the conductivity in the electrode. The specific surface area of the single-walled carbon nanotube unit can be calculated from the nitrogen adsorption at liquid nitrogen temperature (77K) using Bell Japan's BELSORP-mini.
[0049] The carbon nanotube structure can be included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %, particularly 0.03 wt % to 0.3 wt %, and more particularly 0.05 wt % to 0.2 wt %. When the above range is met, since the conductive path of the electrode can be ensured, the life characteristics of the battery can be improved while the electrode resistance is kept at a low level. In contrast, when an electrode is prepared by using a conductive agent dispersion including fully dispersed conventional single-walled carbon nanotube units, the carbon nanotube structure is not included in the electrode active material layer, or even if it is included unintentionally, it will be included in a negligible very low content. In other words, when an electrode is prepared by using a conductive agent dispersion including fully dispersed conventional single-walled carbon nanotube units, the content of the above-mentioned carbon nanotube structure cannot be deduced.
[0050] Regarding the prior art in which an electrode includes a multi-walled carbon nanotube unit, a large content (e.g., greater than 0.5 wt%) of the multi-walled carbon nanotube unit must be used to compensate for the low conductivity of the multi-walled carbon nanotube unit. In addition, in the case of preparing an electrode by using a conductive agent dispersion in which single-walled carbon nanotube units are completely dispersed, the single-walled carbon nanotube unit cannot be used at a low content because the single-walled carbon nanotube unit may be cut.
[0051] In contrast, the carbon nanotube structure included in the electrode of the present invention has a form in which 2 to 5,000 single-walled carbon nanotube units are combined side by side with each other. Therefore, even during the operation of the battery, its length can be well maintained without being cut, so the conductivity of the electrode can be maintained, and due to the high conductivity of the single-walled carbon nanotube unit, the conductivity of the electrode can be smoothly ensured. Therefore, even if the content of the carbon nanotube structure in the electrode is low, the input characteristics, output characteristics and life characteristics of the battery can be excellent.
[0052] Hydrogenated nitrile rubber is a material initially included in the electrode from the conductive agent dispersion required for preparing the electrode slurry. Hydrogenated nitrile rubber helps to smoothly disperse the bundle-shaped carbon nanotubes in the conductive agent dispersion.
[0053] The weight average molecular weight of the hydrogenated nitrile rubber may be 50,000 g / mol to 500,000 g / mol, particularly 100,000 g / mol to 300,000 g / mol. When the above range is met, since the hydrogenated nitrile rubber can easily penetrate between the single-walled carbon nanotube units in the bundle-type carbon nanotubes, a suitable dispersion of the bundle-type carbon nanotubes can be obtained and the phase stability of the conductive agent dispersion can be improved.
[0054] Hydrogenated nitrile rubber can be with 0.1 weight % to 5.0 weight %, particularly 0.1 weight % to 3.0 weight %, and more particularly 0.1 weight % to 3.0 weight %, for example 0.3 weight % to 3.0 weight % amount is included in the electrode active material layer. When meeting the above range, the diameter of the carbon nanotube structure can be properly controlled, the dispersion stability of the carbon nanotube structure in the electrode slurry can be improved, and gelation (gelation) can be prevented by the compatibility between adhesive (particularly PVdF) and hydrogenated nitrile rubber. Therefore, the input characteristics, output characteristics and life characteristics of the battery can be improved.
[0055] The weight ratio of the carbon nanotube structure to the hydrogenated nitrile rubber can be in the range of 1:0.1 to 1:10, especially in the range of 1:1 to 1:5. When the above range is met, the diameter of the carbon nanotube structure can be properly controlled, the dispersion stability of the carbon nanotube structure in the electrode slurry can be further improved, and gelation can be further prevented by the compatibility between the binder (especially PVdF) and the hydrogenated nitrile rubber. Therefore, the input characteristics, output characteristics and life characteristics of the battery can be improved.
[0056] The electrode active material layer may further include a binder. The binder is used to ensure the bonding force between the electrode active material particles or between the electrode active material and the current collector, wherein any binder commonly used in the art can be used, and its type is not particularly limited. The binder may include, for example, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof, any one of them or a mixture of two or more thereof may be used.
[0057] The binder may be included in an amount of 10 wt % or less, preferably 1 wt % to 3 wt % based on the total weight of the electrode active material layer. When the content of the binder satisfies the above range, excellent electrode adhesion can be achieved while minimizing the increase in electrode resistance.
[0058] Method for preparing electrode
[0059] Next, a method for producing an electrode of the present invention will be described.
[0060] The method for preparing an electrode of the present invention comprises: (1) preparing a mixture comprising bundle-type carbon nanotubes, hydrogenated nitrile rubber and a dispersion medium; (2) dispersing the bundle-type carbon nanotubes in the mixture to form a conductive agent dispersion; (3) preparing an electrode slurry comprising the conductive agent dispersion and an electrode active material; and (4) coating the electrode slurry on a current collector and then drying the coated current collector. The electrode of the above embodiment can be prepared by the above method.
[0061] (1) Steps for preparing the mixture
[0062] The mixture can be prepared by injecting bundle-type carbon nanotubes and hydrogenated nitrile rubber into a dispersion medium. In the bundle-type carbon nanotubes, the above-mentioned single-walled carbon nanotube units are agglomerated to exist in the form of bundles, wherein the bundle-type carbon nanotubes generally include more than two single-walled carbon nanotube units. Specifically, the number of carbon nanotube units constituting the bundle-type carbon nanotubes is greater than the number of carbon nanotube units constituting the above-mentioned carbon nanotube structure.
[0063] Since the hydrogenated nitrile rubber is the same as the above-mentioned hydrogenated nitrile rubber, the description is omitted.
[0064] The weight ratio of the bundle-type carbon nanotubes to the hydrogenated nitrile rubber can be in the range of 1:0.1 to 1:10, particularly in the range of 1:1 to 1:5. The diameter of the carbon nanotube structure can be appropriately controlled, the dispersion stability of the carbon nanotube structure in the electrode slurry can be further improved, and gelation can be further prevented by the compatibility between the binder (particularly PVdF) and the hydrogenated nitrile rubber. Therefore, the input characteristics, output characteristics, and life characteristics of the battery can be improved.
[0065] The dispersion medium may include, for example, an amide-based polar organic solvent such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone (NMP); an alcohol such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol or octanol; a glycol such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,5-pentanediol or hexanediol. Alcohol; polyols such as glycerol, trimethylolpropane, pentaerythritol or sorbitol; glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether or tetraethylene glycol monobutyl ether; ketones such as acetone, methyl ethyl ketone, methyl acetone or cyclopentanone; esters such as ethyl acetate, γ-butyrolactone and ε-propiolactone, any one of them or a mixture of two or more of them can be used, but are not limited thereto. Specifically, the dispersion medium can be N-methylpyrrolidone (NMP).
[0066] The solid content in the mixed solution can be in the range of 0.1 wt % to 10 wt %, particularly 1 wt % to 5 wt %. The diameter of the carbon nanotube structure can be appropriately controlled, and the dispersion stability of the carbon nanotube structure in the electrode slurry can be further improved. In addition, the electrode slurry can have a high solid content while maintaining appropriate viscosity and elasticity.
[0067] (2) Step of forming a conductive agent dispersion
[0068] The process of dispersing the bundle-type carbon nanotubes in the mixture can be carried out using a mixing device such as a homogenizer, a bead mill, a ball mill, a basket mill, a grinder, a universal stirrer, a transparent mixer, a pin mill, a TK mixer, or an ultrasonic treatment (sonification) device. Among them, the beads mill method is preferred because the diameter size of the carbon nanotube structure can be controlled, the uniform distribution of the carbon nanotube structure can be achieved, and it has advantages in terms of cost.
[0069] The bead milling method may be as follows: The mixture is added to a container containing beads, and the container is rotated, so that the bundle-type carbon nanotubes can be dispersed.
[0070] In this case, the conditions for performing the bead milling method are as follows.
[0071] The average particle size of the beads may be 0.5 mm to 1.5 mm, particularly 0.5 mm to 1.0 mm. In the case where the range is satisfied, during the dispersion process, the carbon nanotube structure is not broken and its diameter can be appropriately controlled, and a dispersion solution having a uniform composition can be prepared.
[0072] The rotation speed of the container may be 500 to 10,000 RPM, particularly 2,000 to 6,000 RPM. In the case where the range is satisfied, during the dispersion process, the carbon nanotube structure is not broken and its diameter can be appropriately controlled, and a dispersion solution having a uniform composition can be prepared.
[0073] The time for bead milling can be 0.5 hours to 10 hours, particularly 1 hour to 5 hours, and more particularly 1 hour to 2 hours. When the range is met, during the dispersion process, the carbon nanotube structure is not broken and its diameter can be appropriately controlled, and a dispersed solution with a uniform composition can be prepared. The time for bead milling refers to the total time of using bead milling, for example, if bead milling is performed several times, the time for bead milling refers to the total time spent on several bead millings.
[0074] The bead milling conditions are conditions for properly dispersing the bundle-type carbon nanotubes, especially except for the case where the bundle-type carbon nanotubes are completely dispersed into single-chain single-walled carbon nanotubes. That is, the bead milling conditions are conditions for properly dispersing the bundle-type carbon nanotubes to form a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded side by side to each other in the prepared conductive agent dispersion. This can be achieved only when the composition of the mixture, the bead milling conditions, etc. are strictly controlled.
[0075] Through the above process, a conductive agent dispersion including a carbon nanotube structure can be formed.
[0076] (3) Steps for preparing electrode slurry
[0077] When the conductive agent dispersion is prepared through the above process, the electrode active material is mixed with the conductive agent dispersion to form an electrode slurry. In this case, the above-mentioned electrode active material can be used as the electrode active material.
[0078] In addition, as needed, the electrode slurry may further include a binder and a solvent. In this case, the binder of the above embodiment may be used as a binder. The solvent may include, for example, an amide-based polar organic solvent such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone (NMP); alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol or octanol; glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,5-pentanediol or hexanediol; polyols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol ... Polyols such as glycerol, trimethylolpropane, pentaerythritol or sorbitol; glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether or tetraethylene glycol monobutyl ether; ketones such as acetone, methyl ethyl ketone, methyl acetone or cyclopentanone; esters such as ethyl acetate, γ-butyrolactone and ε-propiolactone, any one of them or a mixture of two or more of them can be used, but the present invention is not limited thereto. The solvent may be the same or different from the dispersion medium used in the pre-dispersion, and may preferably be N-methylpyrrolidone (NMP, N-methylpyrrolidone).
[0079] Meanwhile, in this case, the electrode active material may be included in an amount of 70 wt % to 99.5 wt %, preferably 80 wt % to 99 wt %, based on the total solid content in the electrode slurry. When the content of the electrode active material satisfies the above range, excellent energy density, electrode adhesion and conductivity can be achieved.
[0080] In addition, in the case of including the binder, the binder may be included in an amount of 10 wt % or less, specifically 0.5 wt % to 5 wt %, preferably 1 wt % to 3 wt % based on the total solid content in the electrode slurry.
[0081] The solid content in the electrode slurry may be in the range of 60 wt % to 80 wt %, particularly in the range of 65 wt % to 75 wt %. When the above range is satisfied, during the drying period after the electrode slurry is applied, the migration of the conductive agent and the binder due to the evaporation of the solvent may be suppressed, and an electrode having excellent electrode adhesion and conductivity may be prepared. In addition, a high-quality electrode with less deformation during rolling may be prepared.
[0082] (4) Step of forming an electrode active material layer
[0083] Next, an electrode active material layer is formed by applying and drying the electrode slurry prepared as described above. Specifically, the electrode active material layer can be formed by applying the electrode slurry on the electrode current collector and then drying the coated current collector, or the electrode slurry can be cast on a separate support and then the film separated from the support is laminated to the electrode current collector. If necessary, after the electrode active material layer is formed by the above method, a rolling process can be further performed.
[0084] In this case, the drying and rolling may be performed under appropriate conditions in consideration of the physical properties of the finally produced electrode without particular limitation.
[0085] Secondary battery
[0086] Next, a secondary battery according to the present invention will be described.
[0087] The secondary battery according to the present invention includes the electrode of the present invention as described above. In this case, the electrode may be at least one of a positive electrode and a negative electrode. Specifically, the secondary battery according to the present invention may include a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. In this case, at least one of the positive electrode and the negative electrode includes the above-mentioned electrode of the present invention, that is, the electrode active material layer, the electrode active material layer includes an electrode active material, hydrogenated nitrile rubber and a conductive agent, the conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined, and the carbon nanotube structure may be included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %. Preferably, the electrode of the present invention may be a positive electrode. Since the electrode according to the present invention has been described above, a detailed description will be omitted, and only other components will be described below.
[0088] The separator separates the positive electrode and the negative electrode and provides a mobile path for lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is commonly used for secondary batteries. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure of these polymer films having more than two layers as a separator. In addition, a typical porous non-woven fabric can be used, for example, a non-woven fabric formed by a glass fiber or a polyethylene terephthalate fiber having a high melting point. In addition, a coated separator including a ceramic component or a polymer component can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be selectively used.
[0089] The electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that can be used in the preparation of a lithium secondary battery, but is not limited thereto.
[0090] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.
[0091] For example, aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran (franc), 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used as the non-aqueous organic solvent.
[0092] In particular, cyclic carbonates (ethylene carbonate and propylene carbonate) in carbonate-based organic solvents are highly viscous organic solvents that dissociate lithium salts in electrolyte solutions well due to their high dielectric constant, so cyclic carbonates can be preferably used. Since when the cyclic carbonates are mixed with low-viscosity, low-dielectric-constant linear carbonates such as dimethyl carbonate and diethyl carbonate in an appropriate ratio, electrolyte solutions with high conductivity can be prepared, the cyclic carbonates can be more preferably used.
[0093] As the metal salt, a lithium salt may be used, and the lithium salt is a material that is easily soluble in a non-aqueous electrolyte solution, wherein, as an anion of the lithium salt, for example, at least one selected from the group consisting of: F - , Cl -,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .
[0094] In order to improve the life characteristics of the battery, prevent the reduction of the battery capacity, and improve the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, at least one additive may be further included in the electrolyte, for example, a halogenated alkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum chloride.
[0095] The secondary battery according to the present invention as described above has excellent electrode adhesion and excellent lifespan characteristics at high temperatures compared to typical secondary batteries.
[0096] Hereinafter, the present invention will be described in more detail according to specific examples.
[0097] Preparation Example 1: Preparation of Conductive Agent Dispersion
[0098] Bundle-type carbon nanotubes (specific surface area 650 m 2 / g) and hydrogenated nitrile rubber (weight average molecular weight: 260,000 g / mol) were mixed in N-methylpyrrolidone (NMP) as a solvent to prepare a mixture so that the solid content was 2.4% by weight.
[0099] The mixture was stirred by a bead mill method, and the bundle-type carbon nanotubes were dispersed in a solvent to prepare a conductive agent dispersion. In this case, the diameter of the beads was 1 mm, the rotation speed of the stirring container containing the beads was 3,000 RPM, and stirring was performed for 60 minutes. The conductive agent dispersion includes a carbon nanotube structure having a form in which 2 to 5,000 single-walled carbon nanotube units are combined side by side with each other.
[0100] In the conductive agent dispersion, the amount of the carbon nanotube structure was 0.4% by weight, and the amount of the hydrogenated nitrile rubber was 2.0% by weight.
[0101] Preparation Example 2: Preparation of Conductive Agent Dispersion
[0102] A conductive agent dispersion was prepared in the same manner as in Preparation Example 1, except that the conductive agent dispersion was prepared so that in the conductive agent dispersion, the carbon nanotube structure was present in an amount of 0.4 wt % and the hydrogenated nitrile rubber was present in an amount of 0.2 wt %.
[0103] Preparation Example 3: Preparation of Conductive Agent Dispersion
[0104] A conductive agent dispersion was prepared in the same manner as in Preparation Example 1, except that polyvinylidene fluoride (PVdF, Solef-5130) having a weight average molecular weight of 880,000 g / mol was used instead of the hydrogenated nitrile rubber.
[0105] Preparation Example 4: Preparation of Conductive Agent Dispersion
[0106] A conductive agent dispersion was prepared in the same manner as in Preparation Example 1, except that polyvinylidene fluoride (PVdF, KF9700) having a weight average molecular weight of 880,000 g / mol was used instead of hydrogenated nitrile rubber.
[0107] Preparation Example 5: Preparation of Conductive Agent Dispersion
[0108] A conductive agent dispersion was prepared in the same manner as in Preparation Example 1, except that hydrogenated nitrile rubber was not used.
[0109] Preparation Example 6: Preparation of Conductive Agent Dispersion
[0110] A conductive agent dispersion was prepared in the same manner as in Preparation Example 1, except that bundle-type carbon nanotubes (specific surface area of 185 m 2 / g) instead of the bundle-type carbon nanotubes used in Preparation Example 1.
[0111] Test Example 1: Observation of the Dispersion and Formation of Carbon Nanotube Structure in Conductive Agent Dispersion
[0112] For each of Preparation Examples 1 to 6, the dispersion and formation of the carbon nanotube structure were observed by SEM, and the results are shown in Figure 2 and Figure 3 . Figure 2 A to 2E correspond to Preparation Examples 1 to 5, respectively. Figure 3 A corresponds to Preparation Example 1, Figure 3 B corresponds to Preparation Example 6.
[0113] Test Example 2: Evaluation of Formation of Bundled Carbon Nanotubes in Conductive Agent Dispersion
[0114] The conductive agent dispersions of Preparation Examples 1 to 5 were left at 25°C for 2 weeks. The results are shown in Figure 4 .
[0115] Reference Figure 2 In the case of Preparation Examples 1 and 2, it can be seen that there is a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded side by side to each other. In addition, it can be seen that the dispersion of Preparation Examples 1 and 2 using hydrogenated nitrile rubber as a dispersant is better than that of Preparation Examples 3 and 4 using polyvinylidene fluoride and Preparation Example 5 not using a dispersant. In addition, referring to Figure 4 , since the dispersities of Preparation Examples 1 and 2 are better than those of other Preparation Examples, it can be seen that even after long-term placement, the dispersibility remains optimal. In addition, since in Preparation Example 1, 2.0 wt % of hydrogenated nitrile rubber is used, the dispersibility of Preparation Example 1 is better compared with Preparation Example 2 using 0.2 wt % of hydrogenated nitrile rubber.
[0116] Reference Figure 3 , it can be seen that the single-walled carbon nanotube units in the conductive agent dispersion of Preparation Example 1 are not cut and are maintained in a long fiber length, and show high dispersibility. On the other hand, it can be seen that the multi-walled carbon nanotube units in the conductive agent dispersion of Preparation Example 6 are mostly cut and exist only in a length of 1 μm, and even if a dispersion process is applied under the same conditions, its dispersibility is low.
[0117] Therefore, it can be seen that the use of hydrogenated nitrile rubber, its content, and appropriate use of bundle-type carbon nanotubes composed of single-walled carbon nanotube units can improve dispersibility and conductivity.
[0118] Examples and Comparative Examples
[0119] Example 1: Manufacturing positive electrode
[0120] LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622) and a binder (PVDF, KF9700) were added to the conductive agent dispersion of Preparation Example 1, and N-methylpyrrolidone (NMP, N-methylpyrrolidone) was additionally added to prepare a positive electrode slurry having a solid content of 72.0 wt%. The positive electrode slurry was coated on an Al thin film current collector having a thickness of 20 μm, dried at 130° C., and rolled to prepare a positive electrode including a positive electrode active material layer.
[0121] In the positive electrode active material layer, LiNi 0.6 Co 0.2 Mn 0.2 The content of O2 (NCM622) was 97.9 wt %, the content of the binder was 1.8 wt %, the content of the hydrogenated nitrile rubber was 0.25 wt %, and the content of the carbon nanotube structure was 0.05 wt %.
[0122] Reference Figure 1 and Figure 5 A. It can be seen that in the positive electrode of Example 1, the rope-shaped carbon nanotube structure forms a network structure and connects the NCM622 to each other.
[0123] Example 2: Manufacturing the positive electrode
[0124] LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622) and a binder (PVDF, KF9700) were added to the conductive agent dispersion of Preparation Example 1, and N-methylpyrrolidone (NMP, N-methylpyrrolidone) was additionally added to prepare a positive electrode slurry having a solid content of 70.1 wt%. The positive electrode slurry was coated on an Al thin film current collector having a thickness of 20 μm, dried at 130° C., and rolled to prepare a positive electrode including a positive electrode active material layer.
[0125] In the positive electrode active material layer, LiNi 0.6 Co 0.2 Mn 0.2 The content of O2 (NCM622) was 97.6% by weight, the content of the binder was 1.8% by weight, the content of the hydrogenated nitrile rubber was 0.5% by weight, and the content of the carbon nanotube structure was 0.1% by weight.
[0126] Comparative Example 1: Manufacturing positive electrode
[0127] (1) Preparation of conductive agent dispersion
[0128] The specific surface area is 240m 2 / g of carbon black and hydrogenated nitrile rubber (weight average molecular weight: 260,000 g / mol) were mixed with N-methylpyrrolidone (NMP) as a solvent to prepare a mixture having a solid content of 16.5 wt %.
[0129] The mixture was stirred by a bead mill method, and the bundle-type carbon nanotubes were dispersed in a solvent to prepare a conductive agent dispersion. In this case, the diameter of the beads was 1 mm, the rotation speed of the stirring container containing the beads was 3,000 RPM, and stirring was performed for 60 minutes.
[0130] In the conductive agent dispersion, the amount of carbon black was 15% by weight, and the amount of hydrogenated nitrile rubber was 1.5% by weight.
[0131] (2) Preparation of positive electrode
[0132] LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622) and a binder (PVDF, KF9700) were added to the conductive agent dispersion, and N-methylpyrrolidone (NMP, N-methylpyrrolidone) was additionally added to prepare a positive electrode slurry having a solid content of 72.0 wt%. The positive electrode slurry was coated on an Al thin film current collector having a thickness of 20 μm, dried at 130° C., and rolled to prepare a positive electrode including a positive electrode active material layer.
[0133] In the positive electrode active material layer, LiNi 0.6 Co 0.2 Mn 0.2 The content of O2 (NCM622) was 96.35 wt %, the content of the binder was 2.0 wt %, the content of the hydrogenated nitrile rubber was 0.15 wt %, and the content of the carbon black was 1.5 wt %.
[0134] Comparative Example 2: Manufacturing of positive electrode
[0135] LiNi 0.6 Co 0.2 Mn 0.2O2 (NCM622) and a binder (PVDF, KF9700) were added to the conductive agent dispersion of Preparation Example 6, and N-methylpyrrolidone (NMP, N-methylpyrrolidone) was additionally added to prepare a positive electrode slurry having a solid content of 72.1 wt%. The positive electrode slurry was coated on an Al thin film current collector having a thickness of 20 μm, dried at 130° C., and rolled to prepare a positive electrode including a positive electrode active material layer.
[0136] In the positive electrode active material layer, LiNi 0.6 Co 0.2 Mn 0.2 The content of O2 (NCM622) was 97.48 wt %, the content of the binder was 1.8 wt %, the content of the hydrogenated nitrile rubber was 0.12 wt %, and the content of the multi-walled carbon nanotube was 0.6 wt %.
[0137] Comparative Example 3: Manufacturing positive electrode
[0138] LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622) and a binder (PVDF, KF9700) were added to the conductive agent dispersion of Preparation Example 6, and N-methylpyrrolidone (NMP, N-methylpyrrolidone) was additionally added to prepare a positive electrode slurry having a solid content of 71.8 wt%. The positive electrode slurry was coated on an Al thin film current collector having a thickness of 20 μm, dried at 130° C., and rolled to prepare a positive electrode including a positive electrode active material layer.
[0139] In the positive electrode active material layer, LiNi 0.6 Co 0.2 Mn 0.2 The content of O2 (NCM622) was 97.04 wt %, the content of the binder was 2.0 wt %, the content of the hydrogenated nitrile rubber was 0.16 wt %, and the content of the multi-walled carbon nanotube was 0.8 wt %.
[0140] Comparative Example 4: Manufacturing positive electrode
[0141] (1) Preparation of conductive agent dispersion
[0142] Bundle-type carbon nanotubes (specific surface area 650 m 2 / g) and hydrogenated nitrile rubber (weight average molecular weight: 260,000 g / mol) were mixed in N-methylpyrrolidone (NMP) as a solvent to prepare a mixture so that the solid content was 4.4% by weight.
[0143] The mixture was stirred by a bead mill method, and the bundle-type carbon nanotubes were dispersed in a solvent to prepare a conductive agent dispersion. In this case, the diameter of the beads was 1 mm, the rotation speed of the stirring container containing the beads was 3,000 RPM, and when one cycle was stirred for 60 minutes, a total of four cycles were performed (natural cooling for 60 minutes between two cycles).
[0144] In the conductive material dispersion, the amount of the bundle-type carbon nanotube was 0.4% by weight, and the amount of the hydrogenated nitrile rubber was 4.0% by weight.
[0145] (2) Preparation of positive electrode
[0146] LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622) and a binder (PVDF, KF9700) were added to the conductive agent dispersion, and N-methylpyrrolidone (NMP, N-methylpyrrolidone) was additionally added to prepare a positive electrode slurry having a solid content of 72.0 wt%. The positive electrode slurry was coated on an Al thin film current collector having a thickness of 20 μm, dried at 130° C., and rolled to prepare a positive electrode including a positive electrode active material layer.
[0147] In the positive electrode active material layer, LiNi 0.6 Co 0.2 Mn 0.2 The content of O2 (NCM622) is 97.65 wt %, the content of binder is 1.8 wt %, the content of hydrogenated nitrile rubber is 0.5 wt %, and the content of single-walled carbon nanotube is 0.05 wt %. Figure 5 B, no carbon nanotube structure is observed in the positive electrode active material layer, and it can be seen that the single-walled carbon nanotube unit exists alone in the form of a single chain. Figure 5 In B, the single-walled carbon nanotube units are observed to partially overlap, which is not a bonding state, but it is only observed that the single-walled carbon nanotube units overlap above and below the observation direction and have different orientations.
[0148] Experimental Example 1
[0149] Each positive electrode slurry used to prepare the positive electrode of Examples 1 and 2 and Comparative Examples 1 to 4 was dried at 130° C. for 3 hours in a vacuum and then pulverized to prepare a powder. Thereafter, pellets were prepared at 25° C. under a load of 9.8 MPa and in an atmosphere of 50% relative humidity by using a Loresta GP apparatus of Mitsubishi Chemical Analytic Co., Ltd. Then, the powder resistance was measured by a 4-probe method. The measurement results are shown in Table 1 below.
[0150] Experimental Example 2
[0151] The adhesion of each of the positive electrodes prepared in Examples 1 and 2 and Comparative Examples 1 to 4 was measured by a 90° Peel Test method.
[0152] Specifically, a double-sided tape was adhered to a glass slide, an electrode punched out into 20 mm × 180 mm was placed on the glass slide and adhered thereto by reciprocating a 2 kg roller 10 times, and then pulled out at a speed of 200 mm / min by using a UTM (TA company) device to measure the force of peeling from the glass slide. In this case, the measurement angle of the glass slide and the electrode was 90 °. The measurement results are shown in Table 1 below.
[0153] Experimental Example 3
[0154] The single cell was prepared by combining the positive electrode, the negative electrode, and the 15 μm thick polyethylene-based separator prepared according to Examples 1 and 2 and Comparative Examples 1 to 4. In this case, the negative electrode slurry was prepared by mixing graphite, SBR / CMC, and a conductive agent in a weight ratio of 96.5:2.5:1, coating the negative electrode slurry on a 10 μm copper foil and drying it at 100°C to prepare the negative electrode. Then, an electrolyte solution in which 1M LiPF6 was dissolved was injected into a mixed solvent (DEC:EC=1:1) of dimethyl carbonate (DEC) and ethylene carbonate (EC) to manufacture a lithium secondary battery.
[0155] The lithium secondary battery prepared as described above was charged and discharged 60 times at 45° C. at 0.33C / 0.33C, and then life characteristics were measured by using the measured charging efficiency and discharging efficiency. The measurement results are shown in Table 1 below.
[0156] [Table 1]
[0157]
[0158] Referring to Table 1, it can be seen that the electrode adhesion and life characteristics of Examples 1 and 2 including the carbon nanotube structure described in this specification are high, and the powder resistance of the slurry used to manufacture the electrode is low.
[0159] In particular, in the case of Comparative Examples 2 and 3, since the multi-walled carbon nanotube units are cut during the dispersion process, it is difficult to maintain the conductive path, so the powder resistance of the slurry is high, and it is difficult to form a conductive network structure in the electrode, so it appears to have very low electrode adhesion and life characteristics.
[0160] In Comparative Example 4, the bundle-type carbon nanotubes are excessively dispersed, so that the single-walled carbon nanotubes are separated and exist in the electrode in the form of a single chain. In addition, the single-walled carbon nanotubes are cut during the battery manufacturing process and cannot form a network structure like the rope-like carbon nanotube structure, but only exist in close contact with the surface of the electrode active material. Therefore, since the conductive network cannot be smoothly maintained, it can be seen that the slurry powder resistance is high and the electrode adhesion and life characteristics are low.
[0161] The present invention also relates to, for example, the following technical solutions:
[0162] 1. An electrode comprising an electrode active material layer,
[0163] Wherein: the electrode active material layer comprises electrode active material, hydrogenated nitrile rubber and conductive agent;
[0164] The conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are incorporated; and
[0165] The carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %.
[0166] 2. The electrode according to item 1, wherein the carbon nanotube structures are connected to each other to form a network structure in the electrode.
[0167] 3. The electrode according to item 1, wherein in the carbon nanotube structure, the single-walled carbon nanotube units are arranged and combined side by side.
[0168] 4. The electrode according to item 1, wherein the average diameter of the single-walled carbon nanotube units is 0.5 nm to 10 nm.
[0169] 5. The electrode according to item 1, wherein the average length of the single-walled carbon nanotube units is 1 μm to 100 μm.
[0170] 6. The electrode according to claim 1, wherein the specific surface area of the single-walled carbon nanotube unit is 500 m 2 / g to 1,000m 2 / g.
[0171] 7. The electrode according to item 1, wherein the weight average molecular weight of the hydrogenated nitrile rubber is 50,000 g / mol to 500,000 g / mol.
[0172] 8. The electrode according to item 1, wherein the weight ratio of the carbon nanotube structure to the hydrogenated nitrile rubber is 1:0.1 to 1:10.
[0173] 9. An electrode according to item 1, wherein the electrode is a positive electrode.
[0174] 10. A secondary battery, comprising the electrode according to item 1.
Claims
1. An electrode comprising an electrode active material layer, in: The electrode active material layer comprises an electrode active material, hydrogenated nitrile rubber and a conductive agent; The conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are incorporated; wherein the carbon nanotube structures are connected to each other to form a network structure in the electrode; wherein the average diameter of the single-walled carbon nanotube units is 0.5 nm to 9 nm; and The average length of the single-walled carbon nanotube units is 1 μm to 100 μm. 2 . The electrode according to claim 1 , wherein the carbon nanotube structure has a cylindrical structure in which long axes of units are combined in parallel to each other to have flexibility. 3 . The electrode according to claim 1 , wherein in the carbon nanotube structure, the single-walled carbon nanotube units are arranged and combined side by side. 4 . The electrode according to claim 1 , the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %.
5. The electrode according to claim 1, wherein In the carbon nanotube structure, 2 to 4,500 of the single-walled carbon nanotube units are coupled side by side to each other.
6. The electrode according to claim 1, wherein the specific surface area of the single-walled carbon nanotube unit is 500 m 2 / g to 1,000m 2 / g. 7 . The electrode according to claim 1 , wherein the hydrogenated nitrile rubber has a weight average molecular weight of 50,000 g / mol to 500,000 g / mol.
8. The electrode according to claim 1, wherein In the carbon nanotube structure, 2 to 50 of the single-walled carbon nanotube units are combined side by side with each other.
9. The electrode according to claim 1, wherein the electrode is a positive electrode. 10 . A secondary battery comprising the electrode according to claim 1 .
Citation Information
Patent Citations
Compositions comprising 5-cholesten-3, 25-diol, 3-sulfate (25HC3s) or pharmaceutically acceptable salt thereof and at least one cyclic oligosaccharide
KR1020190035776A
